2015
DOI: 10.1371/journal.pone.0118576
|View full text |Cite
|
Sign up to set email alerts
|

Age, Gender and Normalization Covariates for Spinal Cord Gray Matter and Total Cross-Sectional Areas at Cervical and Thoracic Levels: A 2D Phase Sensitive Inversion Recovery Imaging Study

Abstract: The source of inter-subject variability and the influence of age and gender on morphometric characteristics of the spinal cord, such as the total cross-sectional area (TCA), the gray matter (GM) and white matter (WM) areas, currently remain under investigation. Understanding the effect of covariates such as age, gender, brain volumes, and skull- and vertebra-derived metrics on cervical and thoracic spinal cord TCA and GM areas in healthy subjects would be fundamental for exploring compartment specific changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
83
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(112 citation statements)
references
References 46 publications
(69 reference statements)
7
83
3
Order By: Relevance
“…The accuracy has been further validated in the present study in 5 randomly selected patients with ALS and showed satisfactory results (Dice coefficient in the GM ϭ 0.708) in comparison with healthy controls from a previous study 8 (Dice coefficient in the GM ϭ 0.711). Whereas previous studies have reported that the CSA of the SC is associated with morphologic features such as brain volume 29 and total intracranial volume, 30 the correlations were mild, and there is no clear consensus as to what is the best normalization method to use 31 ; several published studies have not performed CSA normalization, 3,26,[31][32][33] and neither did we in the present study. Future work could further investigate methods for normalization, and specifically for the GMCSA.…”
Section: Methodologic Considerationscontrasting
confidence: 85%
See 2 more Smart Citations
“…The accuracy has been further validated in the present study in 5 randomly selected patients with ALS and showed satisfactory results (Dice coefficient in the GM ϭ 0.708) in comparison with healthy controls from a previous study 8 (Dice coefficient in the GM ϭ 0.711). Whereas previous studies have reported that the CSA of the SC is associated with morphologic features such as brain volume 29 and total intracranial volume, 30 the correlations were mild, and there is no clear consensus as to what is the best normalization method to use 31 ; several published studies have not performed CSA normalization, 3,26,[31][32][33] and neither did we in the present study. Future work could further investigate methods for normalization, and specifically for the GMCSA.…”
Section: Methodologic Considerationscontrasting
confidence: 85%
“…As investigated in a previous study, 30 age and sex could affect both SC and GMCSA. In the present study, the controls and patients were age-matched but not sex-matched (number of women, 6 with ALS versus 11 controls).…”
Section: Methodologic Considerationsmentioning
confidence: 67%
See 1 more Smart Citation
“…In multiple sclerosis (MS), these measures in the cervical and thoracic SC have been shown to correlate independently with measures of physical disability . Moreover, it has recently been demonstrated in healthy controls that the sensitivity and specificity of these morphometric assessments could improve further by accounting for the effects of different covariates such as age, gender, brain volumes, and skull‐ and vertebra‐derived metrics …”
Section: Introductionmentioning
confidence: 99%
“…10 A growing body of evidence has determined that spinal cord MRI involvement shows a particularly close association with MSrelated disability. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] In addition, spinal cord involvement manifests early in the disease course; such lesions in presymptomatic at-risk individuals predict conversion to overt MS. 25 Adding more relevance to the need to consider spinal cord involvement in MS is the observation that such involvement may progress independently from the brain.…”
mentioning
confidence: 99%